Acrylamide and 5-hydroxymethylfurfural formation during biscuit baking. Part II: Effect of the ratio of reducing sugars and asparagine. (1st September 2017) - Nguyen, Ha T.; van der Fels-Klerx, H.J. (Ine).; van Boekel, M.A.J.S.
Highlights: Acrylamide and HMF formation in 4 biscuit types baked at 200 °C was studied. Kinetic modelling of acrylamide and HMF formation in the baked biscuits was applied. The "Acrylamide toolbox 2013" is not valid for the role of asparagine in the baked biscuits. Abstract: This study investigated acrylamide and 5-hydroxymethylfurfural (HMF) formation during biscuit baking. Four types of wheat flour with different molar ratios of total fructose and glucose to asparagine were investigated. Nevertheless, the molar ratio in all four biscuit doughs exceeded one after proofing due to enzyme action. Data obtained after baking were used to develop a mechanistic model, based on the asparagine-related pathway, for acrylamide and HMF formation in the four baked biscuit types. Asparagine reacted with fructose to form a Schiff base before decarboxylation to produce acrylamide without Amadori rearrangement product and sugar fragmentation. Fructose contributed considerably to acrylamide formation and to HMF formation via caramelization in all four biscuit types. No clear correlation was found between acrylamide and HMF in baked biscuits, nor between asparagine and the sum of glucose and fructose concentrations in the wheat flour.